2019
DOI: 10.1108/bij-09-2018-0279
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study of challenges and strategies of Indian IT organizations toward global branding

Abstract: Purpose There is a lacuna in research work in terms of understanding how Indian IT organizations can become global brands. Benchmarking has not received much attention in marketing literature due to lack of benchmarking framework, and IT organizations are yet to make progress in benchmarking. The purpose of this paper is to examine the impact of brand strength on global branding by developing a conceptual benchmarking framework for Indian IT organizations. Design/methodology/approach Semi-structured in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 101 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the findings from multiple case study can be hypothesized to a larger extent and collaborate in theory building. Henceforth, a study based on multiple case study is more accurate, logical, and sound (Ray & Sharma, 2019 ). The findings accomplished from multiple case study method are more robust and trustworthy (Baxter & Jack, 2008 ).…”
Section: Methodology and Case Studymentioning
confidence: 99%
“…Furthermore, the findings from multiple case study can be hypothesized to a larger extent and collaborate in theory building. Henceforth, a study based on multiple case study is more accurate, logical, and sound (Ray & Sharma, 2019 ). The findings accomplished from multiple case study method are more robust and trustworthy (Baxter & Jack, 2008 ).…”
Section: Methodology and Case Studymentioning
confidence: 99%
“…In addition, it suggested that the top 500 National Stock Exchange (NSE)/Bombay Stock Exchange (BSE)-listed firms implement integrated reporting (IR) for nonfinancial reporting. These programs have significantly enhanced India’s sustainability disclosure framework (Biswas, 2011; Hossain et al , 2006; Maqbool and Zameer, 2018; Ray and Sharma, 2020). The impact of the substantial changes on sustainability reporting and corporate governance in India is yet to be determined, and further research in this field is required as it is still in its early stages (Kumar et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The symbiotic and collaborative relationship helps in improving the performance (Vimal et al, 2019). The relevant indicators are value enhancement, derived flexibility, investment for a flexible ecosystem, exploitation, entrepreneurship, supply chain integration, comprehensive feedback, brand, relationship, community-building, e-platforms/e-services, leveraging institutional sharing economy among partners, and social engagement (Dubey et al, 2017;Elg et al, 2015;Fauska et al, 2014;Lu et al, 2018;Niu et al, 2009;Patel et al, 2015;Palanisamy and Foshay, 2013;Ray and Sharma, 2019;Saraf et al, 2007;Shukla, 2013Shukla, , 2018Stephenson and McDermid, 2005). The practices and indicators are depicted in Figure 7.…”
Section: Flexibility Maturity Model Architecture and Appraisal Goalsmentioning
confidence: 99%